Paul Moore's Centennial Land Run Monument. Issue 4 (December 2020) - Alt, Gordon
In 2019, Sculptor Paul Moore FNSS completed his monument of the 1889 Centennial Land Run in Oklahoma City, OK. It took him over twenty years to complete this powerful work, which is one of the largest monuments in the world. It stretches over an area slightly larger than a football field and contains forty-five powerful sculptures of horsemen and wagons racing over the Oklahoma landscape of hills and creek. It is a vision that caught the moment after a cannon announced the beginning of the Land Run, in which over 50, 000 individuals took part in an effort to claim land in the Oklahoma Territory. The sculpture contains masterful images of straining horses and frantic individuals caught in a vital effort to succeed in this race to claim valuable homesteads and pastureland. Moore was awarded the Medal of Honor by the National Sculpture Society this past October, partially in regard for this outstanding public work and the quality of sculpture this extraordinarily talented artist has created in his lifetime.